2014
DOI: 10.3174/ajnr.a4060
|View full text |Cite
|
Sign up to set email alerts
|

“Y” and “X” Stent-Assisted Coiling of Complex and Wide-Neck Intracranial Bifurcation Aneurysms

Abstract: BACKGROUND AND PURPOSE: Stent-assisted coiling with two stents has been described in some series for the treatment of complex and wide-neck bifurcation aneurysms. Our aim was to report our experience of a stent-assisted coiling technique with double stents in "Y" and "X" configurations, with emphasis on safety, feasibility, and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
125
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 27 publications
2
125
1
3
Order By: Relevance
“…4,5 However, the risk of procedure-related morbidity and mortality is not negligible, especially with double-stent placement in Y and X configurations. 4,6,7 The widespread adoption of endovascular treatment for MCA aneurysms with unfavorable anatomy requires an improvement of the safety of the endovascular approach. A new device, the pCONus aneurysm implant (phenox, Bochum, Germany), has recently been developed to improve the safety of endovascular treatment of these challenging aneurysms.…”
mentioning
confidence: 99%
“…4,5 However, the risk of procedure-related morbidity and mortality is not negligible, especially with double-stent placement in Y and X configurations. 4,6,7 The widespread adoption of endovascular treatment for MCA aneurysms with unfavorable anatomy requires an improvement of the safety of the endovascular approach. A new device, the pCONus aneurysm implant (phenox, Bochum, Germany), has recently been developed to improve the safety of endovascular treatment of these challenging aneurysms.…”
mentioning
confidence: 99%
“…[8][9][10] However, endovascular treatment of such complex intracranial aneurysms requires the use of complex endovascular techniques with double-stent placement in Y and X configurations. Bartolini et al 11 suggested that Y and X stent-assisted coiling was associated with a high rate of complications, 10% procedure-related permanent morbidity, and 1% mortality rate.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Even in the era of endoluminal and intrasaccular flow diverters, many wide-neck and wide-neck bifurcation aneurysms will continue to be treated with conventional coiling, particularly with stent assistance. [6][7][8] We present the results of a systematic review and metaanalysis examining outcomes of endovascular coiling of wideneck and wide-neck bifurcation aneurysms with and without stent-assisted coiling. The aim of our study was to assess both angiographic and clinical outcomes in order to provide overall data against which current and future emergent techniques can be compared.…”
mentioning
confidence: 99%